Bruegel : defining a dynasty - Orrock, Amy; Bruegel, Pieter, approximately 1525-1569.; Bruegel, Pieter, 1564-1638.; Bruegel, Jan, 1568-1625.; Kessel, Jan van, 1626-1679.; Holburne Museum (London; New York: PWP, 2017)
This accompanying publication will explore the development and diversity of this legendary dynasty of Flemish painters over four generations and 150 years. From the proverb pictures and peasant festivals of Pieter Bruegel the Elder and his eldest son Pieter Brueghel the Younger to the exquisite flower pieces of Jan 'Velvet' Brueghel and the captivating cabinet paintings of Jan van Kessel, the book will unravel the mysteries of the dynasty, and will explore how Bruegel's sons were able to emulate their father's model despite having no access to his paintings. The book will turn the spotlight on to the major Bruegel holdings in UK collections for the first time, telling the story of the dynasty through masterpieces from British public collections and a number of previously unseen works from private collections. Exhibition: Holburne Museum, Bath, UK (11.02.-04.06.2017).
Published to accompany an exhibition of the same name held February 11-June 4, 2017 at the Holburne Museum, Bath.
Includes bibliographical references (pages 110-112) and index.
Keywords: Bruegel, Pieter, -- approximately 1525-1569 -- Exhibitions-ekspozita; Bruegel, Pieter, -- 1564-1638 -- Exhibitions. -- Artet boterore; Bruegel, Jan, -- 1568-1625 -- Exhibitions. -- Arti vizual-piktura; Kessel, Jan van, -- 1626-1679 -- Exhibitions. -- Arti i rilindjes; Bruegel, Jan, -- 1568-1625. -- Artiste hollandezee; Bruegel, Pieter, -- 1564-1638.; Bruegel, Pieter, -- approximately 1525-1569.; Kessel, Jan van, -- 1626-1679.; Piktore hollandeze-Brugel-analiza; Exhibition catalogs; Exhibition catalogs